Characterization and Phytochemical Screening of Rambai Leaf Extract (Baccaurea motleyana Mull.Arg) from Peureulak, Aceh. - M. Alfaruqi; Rani, Zulmai; Indrayani, Gabena; Nasution, Haris Munandar (CV. Nusantara Scientific Medical, 2025)
The rambai plant (Baccaurea motleyana Mull.Arg) contains flavonoid compounds scattered in various parts of the plant such as roots, stems, bark, twigs, leaves, fruit, flowers and seeds. Rambai leaves have various properties that have been empirically proven to cure various diseases, including wound medicine, smallpox medicine, and flu powder. The aim of this research is to find out whether rambai leaf extract contains phytochemicals and to determine the characteristics of rambai leaf extract. Phytochemical screening of rambai leaf extract (Baccaurea motleyana Mull.Arg), including examination of flavonoids, tannins, saponins, steroids/triterpenoids, alkaloids and glycosides. Phytochemical screening was carried out on simplicia powder and simplicia extract and characterization of simplicia was carried out. Testing the water content of rambai leaves was 8%, the water soluble essence content was 33.22%, the ethanol soluble essence content was 13.163% and the total ash content was 5.1% and the acid insoluble ash content was 0.3%. Rambai leaf extract positively contains alkaloids, flavonoids, saponins, tannins, steroids/triterpenoids, and glycosides.